Growing up to Financial Stability - Michael D. Bordo (Economics: The Open-Access, Open-Assessment E-Journal, 2008)
This lecture revisits the evidence on the incidence and severity of different varieties of financial crises within the context of globalization then (pre-1914) and now (1980 to the present). I then discuss the determinants of emerging market crises from the perspective of the recent balance sheet approach. This approach puts at center stage the importance of financial development. I then peel the onion back further and consider the ?deep? institutional determinants of financial development and their relationship to financial stability. I conclude by conjecturing about the ways countries learn from their financial crises to improve their institutions and grow up to financial stability.
Keywords: O1; F4; G2; N1; 330; Financial crises; globalization; financial development; institutions; Internationaler Finanzmarkt; Finanzmarktkrise; Globalisierung; Industriestaaten; Aufstrebende Märkte